2020
DOI: 10.1002/ppul.24985
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette, shisha, and electronic smoking and respiratory symptoms in Swiss children: The LUIS study

Abstract: Background Smoking habits in adolescents are changing. We assessed active smoking of conventional cigarettes, e‐cigarettes and shishas in Swiss schoolchildren, studied risk factors and compared respiratory problems between smokers and non‐smokers. Methods We used data from LuftiBus in the school (LUIS), a school‐based survey of respiratory health of children carried out 2013 to 2016 in the canton of Zurich, Switzerland. Participants were asked about use of cigarettes, shishas, and electronic smoking devices (E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
(98 reference statements)
1
18
0
Order By: Relevance
“…Information was collected by student self‐report and a parental questionnaire. Cough, apart from colds, was reported by 26% of never smokers, 29% of occasional smokers (adjusted OR: 1.3, 95% CI: 1.0–1.7), and 34% of frequent smokers (adjusted OR: 1.7, 95% CI: 0.9–3.2) ( p trend .112) and cough more than others was reported by 4% of never smokers, 4% of occasional smokers (adjusted OR: 1.4, 95% CI: 0.8–2.4), and 8% of frequent smokers (adjusted OR: 3.0, 95% CI: 0.9–9.5) ( p trend .261) 32 …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Information was collected by student self‐report and a parental questionnaire. Cough, apart from colds, was reported by 26% of never smokers, 29% of occasional smokers (adjusted OR: 1.3, 95% CI: 1.0–1.7), and 34% of frequent smokers (adjusted OR: 1.7, 95% CI: 0.9–3.2) ( p trend .112) and cough more than others was reported by 4% of never smokers, 4% of occasional smokers (adjusted OR: 1.4, 95% CI: 0.8–2.4), and 8% of frequent smokers (adjusted OR: 3.0, 95% CI: 0.9–9.5) ( p trend .261) 32 …”
Section: Resultsmentioning
confidence: 97%
“…Ninety‐eight studies were found in the initial search with a further six papers identified by searching the Grey Literature. Seven studies met the inclusion criteria 29–35 . No further studies were found by cross‐checking the reference list of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LUIS will cover knowledge gaps on children’s respiratory health. This dataset allows to determine prevalence of upper and lower respiratory symptoms, to describe lifestyle characteristics like physical activity and smoking [37], and to study associations with lung function. We are able to use information from both parents and children and several lung function tests including markers of ventilatory function (spirometry), ventilation inhomogeneity (DTG-SBW) and Th2 airway inflammation (FeNO), to answer research questions in a comprehensive way [32, 38].…”
Section: Discussionmentioning
confidence: 99%